Social network as the enabler for library services: challenges of Nigerian academic libraries - Emezie, Nkeiru .A.; Nwaohiri, Ngozi Maria (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
Social networks have become new avenues for libraries to interact with their patrons. Social networks allow individuals to join and create a personal profile, then formally connect with other users of the system as social friend. This new concept is precipitated by the emergence of information and communication technologies which has ushered in web tools applications for libraries. In Nigeria, academic libraries are gradually engaging social networks to deliver library services to their patrons. This has become necessary because 21st century library users are resorting to the internet to seek information thus relegating libraries  which are key players in information provisions and services. However, academic libraries are evolving and rebranding their services to reestablish their worth in the information landscape using social networks. This study seeks to examine the role of social networks in enabling library services with a focus on the library of the Federal University of Technology Owerri Nigeria. It discusses the types of services provided by libraries through social networks and further, investigates factors that undermine effective use of social networks in Nigerian academic libraries. A descriptive survey research was adopted for this study while questionnaire was used as data collection instrument. Also, data were analyzed and  presented using percentages, charts and frequency tables.